The Implementation of Think Talk Write Learning Model Through Role Play to Improve English Learning Outcomes Sub Theme Expression for Introducing Others - Muslimah, Nukliriningsih (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2023)
The aim of this research is to improve English learning outcomes for class X KPBS 2 at SMK 7 Semarang through the implementation of the Think Talk Write learning model through role play. This research is classroom action research (PTK), which was carried out in two cycles, namely cycle I and cycle II. This research involved 36 students in class X, KPBS 2 at SMK 7 Semarang. Each cycle includes four phases, namely: (1) planning, (2) implementation, (3) observation, and (4) reflection. The data were analyzed qualitatively and quantitatively. The research results showed that the average initial score in the pre-cycle was 63, with no students completing the minimum completion criteria. This shows that students' English learning outcomes need to be further improved so that the number of students who complete the course can increase. Then, when implementing the Think Talk Write learning model through role-play activities, student learning outcomes in cycle I increased by 78, but the level of learning completion only reached 50%. The results of cycle II showed an increase in student learning outcomes of 87% with a completion rate of 100%, with all students reaching the minimum completion standard. From the results presented, it can be seen that the application of the Think Talk Write learning model through role play has succeeded in improving students' English learning outcomes. Apart from that, in the Think Talk Write learning model through role play, students are able to learn interactively and creatively, so they actively participate during the learning process.